HIGH SCHOOL STUDENTS CONCEPTION PROFILE ON THE CELL MATERIAL IN TUBAN REGENCY USING THREE-TIER TEST METHOD - Nabila, Rana Yumna; Ibrahim, Muslimin (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Conception is a person's understanding of something being observed. Cell material is prone to misconceptions owing to the fact that the material is unable to be sensed, moreover there are many sub-concepts that need to be fully apprehended. This research aims to describe the high school students conception profile on the cell material in Tuban Regency using the Three-Tier Test method, to describe the differences in the conception of high school students on cell material in Tuban Regency, and to describe the differences in the conception profile of students by school area. This is a descriptive-quantitative research using Three-Tier Test instrument. Data collection was carried out online via google form and interviews via google meet. 60 high school students of class XI in Tuban Regency were involved as the target of the research. The results showed that the conception profile of high school students on cell material in Tuban Regency mastered the concept of 53.21%, did not master the concept of 14.01% and misconceptions 32.78%. The highest of school that did not mastering concept was High School 1 Bancar at 31.30% and the highest misconception was High School 3 Tuban at 36.48%. Students experienced the highest misconception on the endocytosis concept, which was 63.33%. The cause of misconceptions is from student itself, worksheet book, and the teacher’s explanation. Keywords: Conception Profile, Cell, Three-Tier Test.